Assessing Tehran health centers administrators \'s attitudes about role and activities of public health nurses - Mohammadi R (Iran University of Medical Sciences, 1989)
This research is a analytical- descriptive study. The aim of this study is determination attitude of health centers authorities in Tehran about roles and activities of community health nurse. The research instrument was a questionnaire with 33 questions that was made by the researcher. The data was collected through visit to research units in health centers. The result of research showed that the majority of research units have positive attitudes about roles and activities of community health nurse. And majority of research units have positive attitudes about being nurses in health centers. Also it was showed that in some cases, have expressed negative or neutral attitudes. In fact however research units have generally positive attitudes about roles and activities of community health nurse, but majority of research units did not agree with independent treatment of some disease, Provision of health services and health centers management by community health nurse.